2022
DOI: 10.3390/jcm11123454
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor XIII Val34Leu Polymorphism in the Prediction of Premature Cardiovascular Events—The Results of Two Meta-Analyses

Abstract: Background: Polymorphisms within the gene that encodes for coagulation factor XIII (FXIII) have been suggested to be involved in the pathogeneses of ischemic stroke (IS) and myocardial infarction (MI). The Val34Leu polymorphism is one of the most commonly analysed FXIII polymorphisms. However, studies on the role of the Val34Leu polymorphism in the aetiology of vascular diseases often show contradictory results. In the present meta-analysis, we aimed to pool data from available articles to assess the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…In contrast, other meta-analyses have suggested that FXIIIA Val34Leu polymorphism is a protective factor for MI generally [ 66 ] and in Caucasians [ 67 ], which was also concluded by recent review articles on this controversial issue [ 68 , 69 ]. Two comprehensive meta-analyses have suggested that being a carrier of the Val34Leu allele and FXIII heterozygotes themselves are associated with a protective effect against premature MI [ 70 ]. Another meta-analysis claimed that the protective effect of the FXIII-A Val34Leu polymorphism could be significantly influenced by interactions between genes and environmental factors [ 71 ].…”
Section: Factor XIII In Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other meta-analyses have suggested that FXIIIA Val34Leu polymorphism is a protective factor for MI generally [ 66 ] and in Caucasians [ 67 ], which was also concluded by recent review articles on this controversial issue [ 68 , 69 ]. Two comprehensive meta-analyses have suggested that being a carrier of the Val34Leu allele and FXIII heterozygotes themselves are associated with a protective effect against premature MI [ 70 ]. Another meta-analysis claimed that the protective effect of the FXIII-A Val34Leu polymorphism could be significantly influenced by interactions between genes and environmental factors [ 71 ].…”
Section: Factor XIII In Myocardial Infarctionmentioning
confidence: 99%
“…A meta-analysis of 8800 individuals found no conclusive evidence linking the FXIII-A Val34Leu polymorphism with IS [ 106 ]. In a different meta-analysis encompassing 627 cases and 1639 controls within the young adult population, no significant association was observed between the FXIII Val34Leu polymorphism and undetermined source IS in any of the genetic models analyzed [ 70 ]. In this line, others concluded that screening for the FXIII Val34Leu polymorphism would not contribute significantly to the risk prediction of cerebrovascular disease [ 68 ].…”
Section: Factor XIII In Ischemic Strokementioning
confidence: 99%
“…Исследования показали более высокую активность FXII у носителей Leu, в то время как гомозиготы по Val обнаруживают снижение активности этого фактора. Полиморфизм Val34Leu FXII также влияет на структуру фибринового сгустка, особенно в присутствии повышенных концентраций фибриногена, делая его намного более плотным [29]. Низкий уровень FXII у недоношенных детей может быть одним из факторов, способствующих относительно более высокой фибринолитической активности, связанной с риском ВЖК [2].…”
Section: генunclassified